A 520 year record of summer sunshine for the eastern European Alps based on stable carbon isotopes in larch tree rings - Danny McCarroll (Climate Dynamics, 2014)
A 520-year stable carbon isotope chronology from tree ring cellulose in high altitude larch trees (Larix decidua Mill.), from the eastern European Alps, correlates more strongly with summer temperature than with summer sunshine hours. However, when instrumental records of temperature and sunshine diverge after AD 1980, the tree ring time series does not follow warming summer temperatures but more closely tracks summer sunshine trends. It is concluded that sunshine is the dominant control on carbon isotope fractionation in these trees, via the influence of photosynthetic rate on the internal partial pressure of CO2, and that high summer (July-August) sunshine hours is a suitable target for climate reconstruction. We thus present the first reconstruction of summer sunshine for the eastern Alps and compare it with the regional temperature evolution.